Quantitative optical coherence microscopy for the in situ investigation of the biofilm - Meleppat, Ratheesh Kumar (2018)
This paper explores the potential of optical coherence microscopy (OCM) for the in situ monitoring of biofilm growth. The quantitative imaging of the early developmental biology of a representative biofilm, Klebsiella pneumonia (KP-1), was performed using a swept source-based Fourier domain OCM system. The growth dynamics of the KP-1 biofilms and their transient response under perturbation was investigated using the enface visualization of microcolonies and their spatial localization. Furthermore, the optical density (OD) and planar density of the biofilms are calculated using an OCM technique and compared with OD and colony forming units measured using standard procedures via the sampling of the flow-cell effluent.